Folic acid conjugated poly(propylene imine) dendrimer as a nanomedicine tool for targeted drug delivery: Bibliometric analysis using google scholar indexed vosviewer - Girsang, Gabriela Chelvina Santiuly; Nandiyanto, Asep Bayu Dani (Research and Social Study Institute, 2023)
By using bibliometric analysis and data mapping with the help of the VOSViewer program, this study aims to examine the breadth of research on the subject of folic acid-conjugated PPI dendrimers for targeted drug delivery. Data was collected from the Google Scholar scientific document database using the Harzing Publish or Perish 8 application. Journal articles containing the keywords